Análise da aplicabilidade do sistema BIM para projetos de estruturas metálicas - Ribeiro, Victoria da Fonseca [UNESP] (My University, 2021)
The technology advancement has caused changes in several areas of expertise, including Civil Engineering, and in this context, Building Information Modeling - BIM emerges with the purpose of promoting better integration of information, generating greater efficiency in construction. In this study, the characteristics of this new technology were studied, as well as the singularities of steel structure projects in order to verify the viability of using BIM in steel structure projects. In addition, three cases were analyzed in order to testify in practice the information acquired in the research and reinforce the basis of the work. It was possible to verify that BIM process is viable for steel structures, bringing both technical and financial benefits in the design of the project, as long as some precautions are taken.

O avanço da tecnologia gerou transformações em várias áreas de atuação, incluindo a Engenharia Civil, e dentro desse contexto surge o Building Information Modeling – BIM, com o objetivo de promover uma maior integração das informações, gerando maior eficiência na construção. Neste estudo, foram estudadas as características desta nova tecnologia assim como as particularidades dos projetos de estruturas metálicas com o intuito de verificar a viabilidade da utilização do BIM em projetos de estruturas metálicas. Adicionalmente, foram analisados três estudos de caso com o objetivo de comprovar na prática as informações obtidas na pesquisa e fortalecer o embasamento do trabalho. Foi possível constatar que o processo BIM é viável para estruturas metálicas, trazendo benefícios tanto técnicos como financeiros na elaboração do projeto, desde que alguns cuidados sejam tomados.
Keywords: Steel structures; Innovation; Viability analysis; Estruturas metálicas; Inovação; BIM; Análise de viabilidade